Translating concerns into action in the foreign language classroom - Jennifer Yamin-Ali (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This study highlights the concerns and research findings of 11 foreign language (FL)student teachers in the secondary school system in a developing country. They were inservice student teachers who were required to engage in action research as part of their professional preparation. Their research experience enabled them to develop new ways of approaching their concerns with regard to developing the communicative competence of their students. In the first instance, action research prompted them to identify a concern in their classrooms. The tools of action research facilitated their exploration of these concerns in that each had to translate the concern into an intervention which they monitored and reported on. The study reports on what these student teachers identified as concerns and why, and describes the teacher’s intervention in each case. Each teacher’s findings are also reported. What is noteworthy is the potential value of action research as a tool for any teacher since the study includes varied types of schools and varied levels